Ovarian Clear Cell Carcinoma which Detected in Ascitic Fluid Smear - Muthia Kamelia; Aswiyanti Asri; Syamel Muhammad (Andalas Obstetrics And Gynecology Journal, 2021)
Objective: To report the case of ovarian clear cell carcinoma with involvement of both ovaries and metastatic to ascitic fluid and the label mass in the bladderMethod: Case Report  Case: A 51 years old female presented with enlarging abdominal with gradual pain. The result of transabdominal sonography were multiple cysts with solid mass, suspected solid cystic ovarian neoplasm and ascites. The patient prepared for laparotomy; optimal debulking surgery, mass resection from bladder. Cytology examination was performed from ascitic fluid and it was confirmed by histopathology examination.Result: Microscopic features on cytology examination of ascitic fluid smear was suggest carcinoma. Histological examination was confirmed the diagnosis and the result was ovarian clear cell carcinoma. Discussion: Ovarian clear cell carcinoma is a rare subtype of epithelial ovarian cancer and comprises about 5-10% of ovarian carcinomas. Clear cell carcinoma tends to occur in the fifth to seventh decades. Cytology examination showed the cellular smear consists of groups of epithelial cells with large nucleus, hyperchromatic, pale-staining, vacuolated cytoplasm. There is also eosinophilic, extracellular substance. The presence of a tumor in ascitic fluid and the label mass in the bladder can categorize become IIB. This determined based on the FIGO’s ovarian tumor staging system.Keywords: ovarian clear cell carcinoma; ascitic fluid.